2011
DOI: 10.1176/appi.neuropsych.23.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Challenge With Bromocriptine One Month After Mild Traumatic Brain Injury: Altered Working Memory and BOLD Response

Abstract: Catecholamines, particularly dopamine, modulate working memory (WM). Altered sensitivity to dopamine might play a role in WM changes observed after traumatic brain injury (TBI). Thirty-one healthy controls (HC) and 26 individuals with mild TBI (MTBI) 1 month after injury were challenged with bromocriptine versus placebo before administration of a verbal WM functional MRI task. Bromocriptine was associated with improved WM performance in the HC but not the MTBI group. On bromocriptine, the MTBI group showed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 3 publications
1
39
0
Order By: Relevance
“…Despite the large efforts to date, neuroimaging methods still lack the individual patient-level sensitivity and specificity to serve as a diagnostic tool for mTBI. Similar to other reviews in this area (Belanger et al, 2007; Hunter et al, 2012; Niogi and Mukherjee, 2010; Prabhu, 2011; Pulsipher et al, 2011), we believe that ultimate motivations for further neuroimaging work are to provide data to predict an individual's recovery, measure her/his transient and persistent cognitive deficits at a level that compliments or exceeds the sensitivity of neuropsychiatric testing, and quantifies the success of cognitive and drug-based interventions (McAllister et al, 2011). In the meantime, the field needs further effort to provide stronger correlative understanding of the relationships between neuroimaging and neuropsychiatry, and simultaneously both types of measures also need improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large efforts to date, neuroimaging methods still lack the individual patient-level sensitivity and specificity to serve as a diagnostic tool for mTBI. Similar to other reviews in this area (Belanger et al, 2007; Hunter et al, 2012; Niogi and Mukherjee, 2010; Prabhu, 2011; Pulsipher et al, 2011), we believe that ultimate motivations for further neuroimaging work are to provide data to predict an individual's recovery, measure her/his transient and persistent cognitive deficits at a level that compliments or exceeds the sensitivity of neuropsychiatric testing, and quantifies the success of cognitive and drug-based interventions (McAllister et al, 2011). In the meantime, the field needs further effort to provide stronger correlative understanding of the relationships between neuroimaging and neuropsychiatry, and simultaneously both types of measures also need improvement.…”
Section: Discussionmentioning
confidence: 99%
“…As variations on this paradigm have been used extensively to study TBI across the spectrum of severity, including several studies of mTBI (e.g., McAllister et al 2002; McAllister, McDonald et al 2004; McAllister et al 2006; McAllister, Flashman et al 2011; McAllister, McDonald et al 2011; Smits et al 2009; Stulemeijer et al 2010), a brief description of the task appears in order. In the version used by McAllister et al, during scanning participants hear a string of consonant letters.…”
Section: Executive/frontal Lobe Functioning After Mtbimentioning
confidence: 99%
“…McAllister et al (McAllister, Flashman et al 2011; McAllister, McDonald et al 2011) have recently reported results from pharmacological challenge studies examining the effects of dopaminergic and alpha-2 adrenergic agents on cognitive functioning and brain activation after mTBI. Based on evidence that altered dopaminergic regulation may play a role in WM deficits after mTBI (for review see (Arnsten 2011; Gamo and Arnsten 2011; McAllister, Flashman et al 2004)), particularly in prefrontal regions (Arnsten et al 1998), these authors (McAllister, Flashman et al 2011) examined the effects of dopamine D 2 receptor agonist bromocriptine (1.25 mg) versus placebo in 26 mTBI patients about 1 month post-injury relative to 31 healthy controls.…”
Section: Intervention After Mtbi: Cognitive Rehabilitation and Pharmamentioning
confidence: 99%
“…Using a task to test the verbal working memory, bromocriptine, a dopamine agonist, was found to improve working memory in controls, but not in TBI patients. This difference was though to arise from activation of cortical and subcortical areas outside of the task-specific region (79). Another study on altered catecholamine responsiveness focused on the effect of guanfacine, an α2 receptor agonist on working memory in 13 patients with mild TBI.…”
Section: Insights Into the Pathophysiology Of Traumatic Brain Injury mentioning
confidence: 99%